S22-3: System Mapping to Explore Determinants of Physical Activity and Evaluate the Wales-Wide 60+ Active Leisure Scheme (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: System mapping has primarily been used to develop theories, design interventions, and understand complex systems. Its use in evaluating leisure schemes or physical activity interventions has only been demonstrated in a few cases. This study used an innovative approach to capture the lived experiences and opinions of older adults across Wales involved in the 60+ Active Leisure Scheme (ALS). As part of the project, system mapping was conducted to better understand the current system and how the 60+ ALS is situated within Wales.Methods: Ten participatory workshops and five semi-structured interviews were held across the regional partnership areas where the 60+ ALS has been implemented. These involved a total of 82 adults aged 60 years or over, along with stakeholders. The workshops and interviews aimed to gather area-specific information on participants’ barriers and facilitators to participating in structured leisure activities, as well as their experiences of additional support from peer volunteers and service providers. Deductive thematic analysis was used to analyse the data, informed by the socio-ecological model. Systems maps were developed to illustrate factors associated with participation in the 60+ ALS. Social network analysis was used to visually represent the position of the 60+ ALS in the wider context and its connectedness to other organisations that regularly signpost or refer participants to leisure activities within the scheme.Results: System maps highlighted physical activity as the main outcome and illustrated how key motivators, barriers, and stakeholder views influence participation in active leisure through the 60+ ALS. The scheme fostered a sense of community and a supportive environment, complementing rather than duplicating existing services. However, greater efforts are needed to engage adults with mobility issues and those in deprived or rural areas.Conclusions: Employing system mapping in the evaluation of a nationwide active leisure scheme proved to be a useful tool and helped identify new approaches to address gaps in delivery. The findings led to development of approaches to refine the delivery and connectedness of the 60+ ALS, as well as the development of strategies to enhance participation among inactive and socially disadvantaged older adults.Support/Funding Source: Nationwide Funding Source: The 60+ Active Voices project was funded by Sport Wales.Keywords: Systems mapping, active leisure, social network analysis